2006
DOI: 10.1002/cncr.22185
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic role of lymph node resection in endometrioid corpus cancer

Abstract: BACKGROUND.The purpose of the current study was to determine the potential therapeutic role of lymphadenectomy in women with endometrioid corpus cancer.METHODS. Demographic and clinicopathologic information were obtained from the Surveillance, Epidemiology, and End Results Program between 1988-2001. Data were analyzed using Kaplan-Meier methods and Cox proportional hazards regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
216
1
21

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(247 citation statements)
references
References 22 publications
9
216
1
21
Order By: Relevance
“…Secondly, patient selection, techniques used to dissect lymph nodes and perform surgery, and postoperative care and follow-up varied substantially across the included studies, which weakens the strength of the conclusions. Thirdly, a previous meta-analysis (40) has shown that, in one of the included trials (26), which accounts for 12,333 of the patients in the population included the present study, body mass index varies significantly between the systematic and no systematic lymphadenectomy groups and that controlling for this leads to a significantly higher OS rate for the systematic lymphadenectomy group than for the no systematic lymphadenectomy group. This highlights the requirement for future studies to control for all possible confounders when examining the clinical effects of systematic lymphadenectomy.…”
Section: Number Of Patientsmentioning
confidence: 72%
See 1 more Smart Citation
“…Secondly, patient selection, techniques used to dissect lymph nodes and perform surgery, and postoperative care and follow-up varied substantially across the included studies, which weakens the strength of the conclusions. Thirdly, a previous meta-analysis (40) has shown that, in one of the included trials (26), which accounts for 12,333 of the patients in the population included the present study, body mass index varies significantly between the systematic and no systematic lymphadenectomy groups and that controlling for this leads to a significantly higher OS rate for the systematic lymphadenectomy group than for the no systematic lymphadenectomy group. This highlights the requirement for future studies to control for all possible confounders when examining the clinical effects of systematic lymphadenectomy.…”
Section: Number Of Patientsmentioning
confidence: 72%
“…As previous studies have emphasized that the number of removed lymph nodes affects survival in patients with endometrial cancer (26,27), the diverse definitions of systematic lymphadenectomy may be the cause of the different efficacies of systematic lymphadenectomy for OS in patients with endometrial cancer. The role of adjuvant radiation in early-stage endometrial cancer is also controversial.…”
Section: Number Of Patientsmentioning
confidence: 99%
“…We observed that 2 patients, who received pelvic lymph node dissection with negative pathology, subsequently developed pelvic recurrences. Nevertheless, Chan et al (2006) reported the therapeutic benefit of lymphadenectomy in women with high grade endometrial cancer, including non-endometrioid patients. Todo et al also reported the therapeutic benefit of pelvic and paraaortic lymphadenectomy over pelvic lymphadenectomy alone in 671 endometrial carcinoma patients (Todo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…So, there is increased evidence against the need to perform systemic lymphadenectomy in low risk cases. 13 What is the extent of lymphadenectomy, whether paraaortic nodes has to be removed or not is controversial. Among patients who underwent systemic pelvic and paraaortic lymphadennectomy 96.2% has negative paraaortic nodes when the pelvic nodes were negative but when pelvic nodes were positive 48% of them had positive paraaortic nodes so paraaortic lymphadenectomy is advised in all high-risk patients or in patients with two or more positive pelvic lymphnodes.…”
Section: Role Of Lymphadenectomymentioning
confidence: 99%